Влияние температуры на содержание различных форм гемоглобина - Тимченко, Н. Н.; Рубакина, В. А.; Евстигнеев, М. П.; Лавриненко, Сергей Николаевич (НТУ "ХПИ", 2015)
Исследовано влияние температуры в области +4-+38°С на спектроскопические свойства гемоглобина в растворах гемолизата при различных сроках хранения гемолизата. Определено содержание различных форм гемоглобина (окси-, дезокси- и метгемоглобина) в растворе гемолизата при различных температурах в зависимости от сроков хранения. Установлено, что при увеличении срока хранения от 1 до 7 дней в растворе гемолизата уменьшается содержание оксигемоглобина и увеличивается содержание дезокси- и метгемоглобина.

The purpose of investigation is studying of temperature influence in the range of +4-+38°C on the hemoglobin spectroscopic properties in hemolysate solutions of different storage terms at +4°C and determining of different forms of hemoglobin contents (oxyhemoglobin, deoxyhemoglobin and methemoglobin). Hemolysate solutions from 1 to 7 days of storage at +4°C were investigated. Different forms of hemoglobin contents (oxyhemoglobin, deoxyhemoglobin and methemoglobin) was determined by special formulas using values of absorbance spectra intensity of hemoglobin at definite wave lengths. There is a quantity of oxyhemoglobin in the hemolysate solution which decreased on the whole as compared to hemolysate of 1 day of storage at increasing of hemolysate solutions storage terms from 1 to 7 days. Thus in control at +4°C the contents of oxyhemoglobin in hemolysate solution of 7 days of storage was less as compared to the contents of oxyhemoglobin in hemolysate solution at +4°C of 1 day of storage. Also the contents of deoxyhemoglobin and methemoglobin in hemolysate solution at 4°C of 7 days of storage was increased. It is possible to associate with the fact that erythrocyte membranes are separated from cells and do not carrying out their save function in hemolysate solutions. It is possible that increase of hemolysate storage terms decrease ability of hemoglobin to binding of oxygen at temperature higher than +20°C. Also these facts can be connected with peculiarity of erythrocytes of donors from which hemolysate solutions were obtained.
Influence of the temperature on the contents of different forms of hemoglobin
Keywords: спектрофотометрический метод; гемолизат; оксигемоглобин; дезоксигемоглобин; метгемоглобин; hemolysate; oxyhemoglobin; deoxyhemoglobin; methemoglobin; temperature